1989
DOI: 10.1128/jvi.63.10.4417-4421.1989
|View full text |Cite
|
Sign up to set email alerts
|

The E6 and E7 genes of the human papillomavirus type 16 together are necessary and sufficient for transformation of primary human keratinocytes

Abstract: The early human papillomavirus type 16 genes that directly participate in the in vitro transformation of primary human keratinocytes have been defined. In the context of the full viral genome, mutations in either the E6 or E7 open reading frame completely abrogated transformation of these cells. Mutations in the El, E2, and E2-E4 open reading frames, on the other hand, had no effect. Thus, both the full-length E6 and E7 genes were required for the induction of keratinocyte immortalization and resistance to ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
368
2
20

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,177 publications
(404 citation statements)
references
References 40 publications
6
368
2
20
Order By: Relevance
“…Since the description of active viral E6/E7 genes in cervical cancer cells (6) and their identification as major HPV oncogenes (10), experimental evidence derived from many studies suggested that expression of the E6 and E7 oncogenes is necessary for the induction and maintenance of the transformed phenotype (2,42). HPV-16 E6-E7 anti-sense RNA inhibits tumorigenicity of cervical cancer cells in nude mice (43), and siRNA targeting of the viral E6/E7 mRNA efficiently kills human papillomavirus-positive cancer cells (44).…”
Section: Discussionmentioning
confidence: 99%
“…Since the description of active viral E6/E7 genes in cervical cancer cells (6) and their identification as major HPV oncogenes (10), experimental evidence derived from many studies suggested that expression of the E6 and E7 oncogenes is necessary for the induction and maintenance of the transformed phenotype (2,42). HPV-16 E6-E7 anti-sense RNA inhibits tumorigenicity of cervical cancer cells in nude mice (43), and siRNA targeting of the viral E6/E7 mRNA efficiently kills human papillomavirus-positive cancer cells (44).…”
Section: Discussionmentioning
confidence: 99%
“…1 Chronic infection of the genital tract by the human papillomavirus (HPV) is the cause of cervical cancer, 2 and the expression of the oncogenic E6 and E7 proteins from HPV is required for the onset and maintenance of malignant transformation. 3 We developed a therapeutic vaccine against cervical cancer based on adenylate cyclase from Bordetella pertussis that carries the HPV E7 oncoprotein (CyaA-E7). This vaccine is able to eradicate palpable tumors generated by the subcutaneous graft of E6/E7-expressing TC-1 cells in a mouse model of cervical cancer.…”
mentioning
confidence: 99%
“…The products of the viral oncogenes E6 and E7 from high-risk viruses have been implicated in carcinogenesis because their expression is sufficient for the immortalization of primary human keratinocytes in vitro. [2][3][4] E6 targets p53 for ubiquitin-mediated degradation, while E7 binds and inactivates the product of the tumor-suppressor gene Rb. 5,6 Despite this efficient program for inactivating tumor-suppressor proteins, development of cervical carcinoma is a multistep process for which E6 and E7 are necessary but not sufficient.…”
mentioning
confidence: 99%